Is there a gender wage gap in online labour markets? Evidence from over 250,000 projects and 2.5 million wage bill proposals - Estrella Gomez-Herrera; Frank Müller-Langer (European Commission, Joint Research Centre (JRC), 2019)
We explore whether there is a gender wage gap in one of the largest EU online labor markets. We provide empirical evidence for a statistically significant 4% gender wage gap among workers. We also find that female workers propose lower wage bills and are more likely to win the competition for contracts. Once we include workers' wage bill proposals in the regressions, the gender wage gap virtually disappears, i.e., it is statistically insignificant and very small in magnitude (0.3%). Our results also suggest that female workers' higher winning probabilities associated with lower wage bill proposals lead to higher expected revenues.
Keywords: D40; J40; 330; Gender wage gap; online labor markets; digitally performable projects